Use of Friction Stir Processing for Improving Heat-Affected Zone Liquation Cracking Resistance of a Cast Magnesium Alloy AZ91D - Karthik, G. M.; Janaki Ram, G. D.; Kottada, Ravi Sankar (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2017)
In this work, a cast magnesium alloy AZ91D was friction stir processed. Detailed microstructural studies and Gleeble hot ductility tests were conducted on the as-cast and the FSPed samples to comparatively assess their heat-affected zone liquation cracking behavior. The results show that the use of FSP as a pretreatment to fusion welding can strikingly improve the heat-affected zone liquation cracking resistance of alloy AZ91D by reducing the amount and size of the low-melting eutectic β (Mg 17 Al 12 ) as well as by refining the matrix grain size.